Analysis of Criminal Policy against Perpetrators of Terrorism Crimes: Perspectives on the Death Penalty and Human Rights in Indonesia - Prabowo, Agung; Amal, Moh Alfi; Pirdaus, Dede Irman (Communication in Research and Publications (CRP), 2023)
The extent of the terrorist network in Indonesia threatens the threat and integrity of the Republic of Indonesia, manifested in broad trends, organization and systematic networks. Terrorist attacks are increasingly brutal, targeting innocent civilians. The threat is increasingly complex with increasing radicalization and online recruitment, requiring comprehensive action, including cooperation with government agencies, security forces, intelligence, and civil society, as well as a comprehensive approach involving intelligence, community participation, and addressing the root causes of radicalization to eradicate terrorist networks . Eradicating criminal acts of terrorism is a serious challenge for the Indonesian government, with one of the complicated aspects being the implementation of the death penalty against perpetrators of terrorism. This article analyzes Indonesian criminal policy, explains the method of punishment, the Human Rights (HAM) perspective, and critical views on the death penalty. In conclusion, it is important to strike a balance between efforts to enforce the death law and the desire for the principles of human rights and justice in the context of eradicating terrorism. Continuous evaluation of the application of the death law and open dialogue involving various parties are the keys to reaching an agreement that upholds humanitarian values and justice in efforts to overcome criminal acts of terrorism in Indonesia.